Кадрове забезпечення шкіл Рівненщини (друга половина 1940-х — перша половина 1950-х років) - Мащенко, Наталія; Mashchenko, Natalija (My University, 2015)
У статті розглянуто кількісно-якісні показники кадрового забезпечення загальноосвітніх шкіл Ровенської області в повоєнне десятиріччя. Аналізуються проблеми та шляхи подолання кадрового дефіциту в навчальних закладах регіону.In article considered a problem of staffing in schools of Rivne region in first postwar decade. Organizing a work in schools of Rivne region, soviet authorities face with the problem of shortage of teaching staff. Main sources replenishment of teaching staff became teaching schools, pedagogical colleges, teachers universities and staff expansion of teachers from the east regions of USSR. However, most of teachers had a low qualification, what adversely effected on a quality of teaching.
Stuffing in Schools of Rivne Region in Second Half 1940th - first Half 1950th
Keywords: педагогіна інтелігенція; кадрова політика; освіта; educational elite; HR policy; education; school; Rivne region